EFFECT OF HERBAL DRUGS ON ESTRUS PERFORMANCE IN SWINE - KUMAR, s; SINHA, A K; SINGH, B; SINHA, M P; MAHTO, DINESH (The Indian Journal of Animal Reproduction, 2023)
During the present study four herbal drugs (Clemenstol syrup, Femelin, Lecorin Plus and Asoka Cordial) were administered orally to 75 gilts and sows at various stages of reproduction to see their effect on estrus performance. The average duration for expression of estrus and fertile estrus were shorter in treated gilts with Clemenstol. Averaged uration for corresponding features were also shorter in all the treated groups of sows which was shortest in Lecorin Plus treated treated group followed by Asoka Cordial and Femelin treated group. However, the differences in duration were non-significant in both gilts and sows.